Emma [videorecording (DVD)] - Glenister, John; Godwin, Doran; Carson, John, 1927-2016-; Eccles, Donald, 1908-1986; Chapman, Constance, 1912-2003; Bowen, Debbie; Austen, Jane, 1775-1817 (BBC Video ; Warner Home Video, 2004)
An adaptation of Jane Austen's novel about Emma Woodhouse, a congenial young lady who delights in meddling in other people's affairs. She is perpetually trying to unite men and women who are utterly wrong for each other. Despite her interest in romance, Emma is clueless about her own feelings, and her relationship with Mr. Knightly.